Synthesis and performances of polyamide forward osmosis membrane for humic acid removal - Mohammad Amirul, Mohd Yusof (2014)
Forward osmosis is a one of develop water treatment method that can be used. Forward osmosis is a process that depends on the concentration gradient and also osmotic potential to treat water which is currently, applicable in many industries. This research focuses on the synthesis and performances of polyamide forward osmosis membrane in order to provide the optimum effect in treating wastewater. This research also used sodium chloride as draw solution due to the highest performances recorded by previous researchers on forward osmosis experiment. This research was conducted based on one parameter which will impact the water flux and overall performances of forward osmosis which is the reaction time of polyamide membrane where, there are three different polyamide forward osmosis membranes with different reaction time with mphenylene diamine (MPD) and trimesoyl chloride (TMC). This research also measures the humic acid rejection for each polyamide forward osmosis membrane by using livVis spectrometer. Besides, reverse salt diffusion caused by different type of polyamide membrane was also tested in terms of conductivity to determine the best performing polyamide membrane. This research was conducted by using ultrafiltration membrane that reacted by twomonomers which are MPDand—TMC-with three different reaction times-(10s,_3 Os, and 60s) to separate the feed and draw solution and the permeation module was constructed as the preliminary laboratory work. Based on the results obtained,increase in molarity of draw solution is proportional to the increasing of water flux.In addition, the increasing of polyamide forward osmosis membrane reaction time with monomer also leads to decreasing of water flux. The water flux obtained by using related formula showed the highest results with polyamide membrane with reaction time of lOs at 2.548 L/m 2h at 2.5M of draw solution whereas the lowest water flux recorded by polyamide membrane with reaction time of 60s at 1.976 L/m 2h at the same concentration of draw solution. Besides that, calculation shows that the increasing of draw solution concentration causes a decreasing in humic acid rejection. However, the data recorded showed that draw-solution at concentrations of 05M to 2.OM has good humic acid rejection at approximately 95%. Based on the discussion, it is found that this research showed polyamide forward osmosis membrane with reaction time of 30s as the best forward osmosis membrane in treating water using forward osmosis process.